Blockchain for business : a practical guide for the next frontier - Kalfoglou, Yannis, 1970- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book sets out to explain blockchain for the non-technical expert, to decipher the dense technicalities that dominate the field, and present the opportunities for busy professionals using practical applications and case studies. Presented in a clear and structured way, and with documented, real-world cases, the book is a practical reference guide that can be used across different industries. It offers both a constructive and critical review of the pain points blockchain is facing today, illustrates the pitfalls as well as the opportunities for business, and describes the steps towards overcoming them. It also aims to provide a unique view of both the intersection and synergy of blockchain with other emerging technologies and the wider digital ecosystem, as we see increasingly that blockchain alone won't be able to deliver business solutions. Most importantly, the book identifies trends and a pathway for the future of blockchain and its impact on society as a whole. The book is written for business audiences across all sectors. It is not a technical guide to blockchain, but enables businesspeople to be better informed and prepared to plan ahead and develop strategies using blockchain"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases) -- Industrial applications; Database management; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Information Management; BUSINESS & ECONOMICS / Development / Sustainable Development